Administrative and legal regulation of greenhouse gas emissions in the framework of a regional experiment - A. S. Matnenko; D. A. Gershinkova (Правоприменение, 2023)
A legal experiment refers to approbation of legislative novelties on a limited scale and covering a limited number of people aiming at assessing effectiveness and usefulness of novelties in order to determine optimal options for future commonly applicable law-making decisions. During the Soviet period, legal experiments were conducted in a systematic manner. The scientific concept of the experiment was in place, including the methodology of conducting the experiment, goal setting, principles of the experimental legal regime, its stages, and results’ evaluation. Today, legal experiments are not regulated. The criteria and principles for conducting legal experiments are formulated mostly for the scientific field. Nevertheless, there are some emerging legal forms where definitions and procedures for conducting experiments are being legally codified. This may be a sign of the emergence of a new direction in the development of the administrative laws. Experiments are conducted in various areas of legal relations, such as economics and finance, culture, environmental and social spheres, digitalization, ets. A recent example of a legal experiment in the environmental sphere is the Law on conducting an experiment on limiting greenhouse gas emissions in some regions of Russia, which was adopted in 2022. The experiment will continue until 2028. It involves introduction of a pilot cap and trade system. Sakhalin region has been chosen for its piloting. Cap and trade system is being introduced for key regional emitters – regional regulated organizations (RRO) in an attempt to achieve carbon neutrality of the Sakhalin Region by 2025. The analysis of the pilot regulatory framework for the Sakhalin experiment has led to the following conclusions:– the experiment is based on a combination of administrative and civil law norms; – generally speaking, the pilot regulatory framework in the Sakhalin Region meets the main criteria for conducting the experiment. However, lack of a clear system for evaluating its results and uncertainty regarding its further application in the country are significant drawbacks;– the use of quotas as one of the administrative and legal methods of regulation is being tested. A comprehensive experiment could involve testing other methods in order to identify the most effective approach for greenhouse gas emissions’ reduction. The option of paying a fixed amount (1000 rubles) for exceeding the quota represents a quasi-tax, which can be seen as a separate regulatory method;– the state support measures are a counterweight of the additional financial burden put on the RRO and should be specified is dedicated normative acts. Substantial support measures may potentially allow for replacement of a special coefficient that reflects the amount of the tax payed by RRO used in the quota calculation methodology and thus help to ensure harmonization with foreign analogues.